Non-Coding RNAs in Oral Diseases: From Pathogenesis to Clinical Translation - Letong Huang; Hailong Zhang; Yi Huang; Ting Lu; Maoyuan Zeng; Haobin Wu; Junhao An; Bin Chen; Jianguo Liu; Qunli Ren (International Journal of Molecular Sciences, 2026)
Oral diseases represent a major global health burden, and non-coding RNAs (ncRNAs) have emerged as pivotal regulators in their pathogenesis, offering new avenues for diagnosis and therapy. This review synthesizes current knowledge on ncRNAs—including miRNAs, lncRNAs, and circRNAs—across a spectrum of oral conditions, encompassing periodontitis, oral squamous cell carcinoma, oral submucous fibrosis, oral lichen planus, oral leukoplakia, and chronic orofacial pain. Mechanistically, ncRNAs function through competing endogenous RNA networks, immune–inflammatory cascades, metabolic reprogramming, and fibroblast activation; notably, recent discoveries have revealed that certain circRNAs and lncRNAs encode functional micropeptides, adding an additional layer of regulatory complexity in oral pathology. On the translational front, salivary and circulating ncRNAs have shown promise as non-invasive biomarkers. However, major bottlenecks remain, including insufficient longitudinal validation, marked technical heterogeneity across studies, and delivery challenges specific to the oral microenvironment. By critically evaluating mechanistic insights alongside these translational barriers, this review identifies critical knowledge gaps and proposes prioritized strategies to facilitate the clinical integration of ncRNA-based precision dentistry.